Reliability of power output during short-duration maximal-intensity intermittent cycling - Glaister, M.; Stone, M. H.; Stewart, A. M.; Hughes, M. (The Journal of Strength and Conditioning Research, 2003)
The aims of the present study were: (a) to determine the number of familiarization trials required to establish a high degree of reliability in measures of power output during maximal intermittent cycling; and (b) to examine the reliability of those same measures after familiarization had been established. On separate days over a 3-week period, 2 groups of 7 recreationally active men completed 8 trials of 1 of 2 maximal (20 × 5-second) intermittent cycling tests with contrasting recovery periods (10-seconds or 30-seconds). Significant (p < 0.05) between-trial differences were detected in post-hoc tests involving trials 1 and 2 only. Within-subject test-retest reliability was therefore assessed across trials 3-8. Apart from values of maximum power output in Protocol 1 (10-second recovery periods), all remaining measures of power output showed high degrees of within-subject test-retest reliability (coefficient of variation: 2.4-3.7%). The results of the present study indicate that in subjects unfamiliar with maximal intermittent cycling, high degrees of reliability in many performance measures can be achieved following the completion of 2 familiarization trials.